(untitled) (PANGEEA, 2025)
Aspects regarding the impact of tourism on the environment in Praid balneary resort. Tourism, more than any other field of activity, is dependent on the natural and the anthropic environment, which is the object and the field of activity of tourism, being the framework support of its resources. The tourism potential being an integral part of the environment, its existence and development depend directly on its quality. The destructive actions of some tourist activities are mainly manifested by the inappropriate exploitation of the recreational environment, amplified by man’s brutal intervention on natural resources and last but not at least on the landscape. These destructive practices are mainly encountered in areas with high tourist potential, or in the proximity of urban settlements. The intensification of tourist activities in increasingly varied forms, and the qualitative and quantitative mismatch between the tourism resources and their exploitation, lead to medium and long-term dysfunctions with repercussions both on the environment and on the tourist industry.